If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3x+4=-1/2x+4
We move all terms to the left:
-3x+4-(-1/2x+4)=0
Domain of the equation: 2x+4)!=0We get rid of parentheses
x∈R
-3x+1/2x-4+4=0
We multiply all the terms by the denominator
-3x*2x-4*2x+4*2x+1=0
Wy multiply elements
-6x^2-8x+8x+1=0
We add all the numbers together, and all the variables
-6x^2+1=0
a = -6; b = 0; c = +1;
Δ = b2-4ac
Δ = 02-4·(-6)·1
Δ = 24
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{24}=\sqrt{4*6}=\sqrt{4}*\sqrt{6}=2\sqrt{6}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-2\sqrt{6}}{2*-6}=\frac{0-2\sqrt{6}}{-12} =-\frac{2\sqrt{6}}{-12} =-\frac{\sqrt{6}}{-6} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+2\sqrt{6}}{2*-6}=\frac{0+2\sqrt{6}}{-12} =\frac{2\sqrt{6}}{-12} =\frac{\sqrt{6}}{-6} $
| 13x-6=11x+12 | | 7(2x-8)=-70 | | 9(2x+5)+5=6+3x | | -x-3-3=-x-2-4 | | -135=-8(p+8)-7 | | 5n=3n-n+5=26 | | 1x-20+137=180 | | 3x+8+3x=5=(x+3)-7 | | 14.6-x÷2.8=7.1 | | -259=5+6(-8-6n) | | 2(6-7m)+2=-98 | | -3(4-x)+2(x+5)=9x+22 | | -3(8m-7)+8=125 | | 9x+4=113 | | -8(2m-8)+4=180 | | 5x(x+1)+6=0 | | x+105=95 | | -8(8m-7)+8=125 | | 6(-7+7x)=252 | | 1+x+3x=17 | | 8(-2+8p)+4=116 | | -15+9+-20x+3+-40x+18=180 | | 5=10x-20 | | Y-5=-3D+6y | | -2(7a-6)+5a=84 | | X^2+4x40=180 | | 7.99×3x=72.83 | | -9n+7n=-2n | | -8(x-8)-2=126 | | 5-3A=7a-5 | | 13.21+0.11(x+3)=13.71-0.08 | | 3x+12=5x-32 |